2021
DOI: 10.1007/s10787-021-00841-8
|View full text |Cite
|
Sign up to set email alerts
|

Boswellic acids/Boswellia serrata extract as a potential COVID-19 therapeutic agent in the elderly

Abstract: The most severe cases of COVID-19, and the highest rates of death, are among the elderly. There is an urgent need to search for an agent to treat the disease and control its progression. Boswellia serrata is traditionally used to treat chronic inflammatory diseases of the lung. This review aims to highlight currently published research that has shown evidence of potential therapeutic effects of boswellic acids (BA) and B. serrata extract against COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 138 publications
1
28
0
2
Order By: Relevance
“…With the advantage of being a natural compound, and certain pharmacological studies showed no harmful side effects, these novel compounds could be a good choice to be used for the treatment of COVID-19 patients. This study is in concordance to important antecedents with boswellic and glycyrrhinic acids against SARS-CoV2 and could be a probable treatment of COVID-19 ( Caliebe et al, 2021 ; Gomaa et al, 2021 ; Li et al, 2021 ; Roy and Menon, 2021 ; Sun et al, 2021 ; van de Sand et al, 2021 ; Yu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…With the advantage of being a natural compound, and certain pharmacological studies showed no harmful side effects, these novel compounds could be a good choice to be used for the treatment of COVID-19 patients. This study is in concordance to important antecedents with boswellic and glycyrrhinic acids against SARS-CoV2 and could be a probable treatment of COVID-19 ( Caliebe et al, 2021 ; Gomaa et al, 2021 ; Li et al, 2021 ; Roy and Menon, 2021 ; Sun et al, 2021 ; van de Sand et al, 2021 ; Yu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
“…Eventually with increasing concentration from 50 to 100 µg/ml noticeable structural loss was observed by both these β-boswellic and glycyrrhicic acids. This might be the possible reason for the loss of activity in SARS-CoV-2 E. Effect on the active site of the SARS-CoV-2 E after binding by these acids was noticed ( Gomaa et al, 2021 ; Sun et al, 2021 ; van de Sand et al, 2021 ). Hence the fluorescence quenching in both β-boswellic and glycyrrhicic acids indicated major changes in the immediate microenvironment of the SARS-CoV-2 E protein.…”
Section: Resultsmentioning
confidence: 99%
“…Licorice extract and Boswellia Serrata gum have pharmacological properties which could support the therapeutic approach for COVID-19. Their antiviral, anti-inflammatory, anti-lung damage, anti-bacteria, antithrombic development, and immunostimulatory properties are all well-known and extensively utilized [ 74 , 75 ]. Another research in the phase 2/3 of the study proposed to study the immunity to COVID-19 with different treatment methods.…”
Section: Natural Products As Medicines For Covid-19mentioning
confidence: 99%
“…We discussed the rationale for the use of licorice extract and boswellia extract for the treatment of COVID-19, focusing on the antiviral effect against SARS-CoV-2 and the control of systemic inflammation and immune dysregulation caused by SARS-CoV-2 infection ( Gomaa et al 2021 ; Gomaa and Abdel-Wadood 2021 ). Recently, van de Sand et al ( 2021 ) suggested that the consumption of products containing glycyrrhizin may be of great benefit to people infected with SARS-CoV-2 as it effectively inhibits SARS-CoV-2 replication in vitro by blocking the main viral protease M pro essential for viral replication.…”
Section: Introductionmentioning
confidence: 99%